2019
DOI: 10.1111/nuf.12330
|View full text |Cite
|
Sign up to set email alerts
|

Transition experiences of newly graduated Filipino nurses in a resource‐scarce rural health care setting: A qualitative study

Abstract: Problem: Without a doubt, the transition to a professional nursing role is a challenging and stressful experience for many new nurses, regardless of where they are employed; yet, no study has been conducted to comprehend in detail the transition experiences of newly graduated nurses employed in a resource-scarce rural health care setting.Purpose: This study describes the transition experiences of newly graduated Filipino nurses during their initial clinical placement process.Methods: A qualitative phenomenolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 67 publications
1
17
0
1
Order By: Relevance
“…Nurses who were relatively new to the profession tended to be silent more as opposed to those who were in the profession for longer. This finding may be explained by the fact that new nurses are not yet familiar with organisational processes and culture and have not yet internalized the organisational structure and operations (Labrague, McEnroe-Pettite, & Leocadio, 2019;van Rooyen, Jordan, ten Ham-Baloyi, & Caka, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses who were relatively new to the profession tended to be silent more as opposed to those who were in the profession for longer. This finding may be explained by the fact that new nurses are not yet familiar with organisational processes and culture and have not yet internalized the organisational structure and operations (Labrague, McEnroe-Pettite, & Leocadio, 2019;van Rooyen, Jordan, ten Ham-Baloyi, & Caka, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Nurses who were relatively new to the profession tended to be silent more as opposed to those who were in the profession for longer. This finding may be explained by the fact that new nurses are not yet familiar with organisational processes and culture and have not yet internalized the organisational structure and operations (Labrague, McEnroe‐Pettite, & Leocadio, 2019; van Rooyen, Jordan, ten Ham‐Baloyi, & Caka, 2018). Furthermore, as a result of being new to the profession, early‐career nurses might be apprehensive regarding speaking up due to the fear of losing their jobs and/or experiencing confrontations with other staff members.…”
Section: Discussionmentioning
confidence: 99%
“…Practicing autonomy and being fully responsible and accountable for their actions were described by the new graduate nurses as tough and hard. Transition shock, feeling pressured, learning excitement, and needing support were also the emerging themes in the transition experiences reported in a qualitative study among new graduate Filipino nurses (Labrague, McEnroe-Pettite, & Leocadio, 2019). Other studies conducted in other countries among new graduate nurses in the United States (Fink, Krugman, Casey, & Goode, 2008); New Zealand (Walton et al, 2018), Australia (Kelly & Ahern, 2009;Ankers, Barton, & Parry, 2018), Hongkong (Wong et al, 2018), and Oman (Al Awaisi, Cooke, & Pryjmachuk, 2015) reported similar themes about transition difficulties and positive experiences in the first year of practice.…”
Section: Resultsmentioning
confidence: 91%
“…As reinforced by a wealth of literature (Dyess & Sherman, 2009;Hofler & Thomas, 2016;Hussein et al, 2017;Wildermuth, Weltin, & Simmons 2019;Labrague et al, 2019), support during the transition period is vital for new graduate nurses. New graduate Filipino nurses considered support from their supervisor, co-staff nurses, senior staff, coworkers, mentors, family, and friends as essential in coping through their transition.…”
Section: Resultsmentioning
confidence: 99%
“…Expectations: New health professionals reported feeling overwhelmed by unrealistically high expectations placed on them (3,13,25,26,29). Labrague et al (3) reported that new health professionals felt pressured and stressed when unachievable expectations were placed on them. Nurses in Clare & Loon's (5) study expressed gratitude to their superiors for having realistic expectations of their skills.…”
Section: Theme 1: Systems and Structuresmentioning
confidence: 99%